Structure-Based Primer Design Minimizes the Risk of PCR Failure Caused by SARS-CoV-2 Mutations - Dong, Hongjie; Wang, Shuai; Zhang, Junmei; Zhang, Kundi; Zhang, Fengyu; Wang, Hongwei; Xie, Shiling; Hu, Wei; Gu, Lichuan (Frontiers in Cellular and Infection Microbiology, 2021)
The coronavirus disease 2019 (COVID-19) has caused and is still causing tremendous damage to the global economy and human health. Quantitative reverse transcription-PCR (RT-qPCR) is the golden standard for COVID-19 test. However, the SARS-CoV-2 variants may not only make vaccine less effective but also evade RT-qPCR test. Here we suggest an innovative primer design strategy for RT-qPCR test of SARS-CoV-2. The principle is the primers should be designed based on both the nucleic acid sequence and the structure of the protein encoded. The three nucleotides closest to the 3' end of the primer should be the codon which encode the tryptophan in the structure core. Based on this principle we designed a pair of primers targeting the nucleocapsid (N) gene. Since tryptophan is encoded by only one codon, any mutation occurs at this position would change the amino acid residue resulting in an unstable N protein. This means this kind of SARS-CoV-2 variant could not survive. In addition, both our data and previous reports all indicate that the mutations occur at other places in primers do not significantly affect RT-qPCR result. Consequently, no SARS-CoV-2 variant can escape detection by RT-qPCR kit containing the primers designed based on our strategy.